Factors Associated with Poor Hemoglobin A1c Control in Patients with Type 2 Diabetes - Alqudah, Salam; Jarab, Anan S.; Alefishat, Eman A.; Mayyas, Fadia; Khdour, Maher; Pinto, Sharrel (Current Diabetes Reviews, 2019)
Background: The limited implementation of clinical pharmacy service programs and the lack of studies identifying barriers to achieve blood glucose control have all attributed to the increased proportion of type 2 diabetes patients who have poor glycemic control in Jordan. Objective: To explore factors associated with higher HbA1c in patients with type 2 diabetes in Jordan. Methods: Variables including socio-demographics, disease and treatment factors were collected from171 patients with type2 diabetes at an outpatient diabetes clinic in Amman. Validated questionnaires were used to assess medication adherence, self-care activities, diabetes knowledge and healthrelated quality of life in addition to data collected from medical records. After the single-predictor analysis, stepwise linear regression was performed to develop a model with variables that best predicted hemoglobin A1c. Results: Medication adherence was inversely associated with HbA1c values (β = -0.275; t = 2.666; P < 0.01), indicating better glycemic control. Receiving insulin therapy was also associated with less HbA1c values and better glycemic control (β = - 0.184; t = 2.080; P < 0.05). Patients who had one or more comorbid conditions (β = 0.215; t = 2.264; P < 0.05) and those with longer diabetes duration (β = 0.092; t = 1.339; P < 0.05) were found to have significantly higher HbA1c values. Conclusion: Emphasizing medication adherence, particularly for patients with longer duration of diabetes and those with multiple comorbid diseases should be strongly considered in future diabetes management programs implemented to improve glycemic control in patients with type 2 diabetes.
Keywords: clinical pharmacy